Sphingosine 1-Phosphate: A Novel Target for Lung Disorders - Mohammed, Sabira; Harikumar, K. B. (Frontiers in Immunology, 2017)
Sphingosine 1-phosphate (S1P) is involved in a wide range of cellular processes which include proliferation, apoptosis, lymphocyte egress, endothelial barrier function, angiogenesis, and inflammation. S1P is produced by two isoenzymes namely, sphingosine kinase 1 and 2 (SphK1 and 2) and once produced, S1P can act both in an autocrine and paracrine manner. S1P can be dephosphorylated back to Sphingosine by two phosphatases (SGPP 1 and 2) or can be irreversibly cleaved by S1P lyase. Sphingosine 1-phosphate has a diverse range of functions which is mediated in a receptor dependent, through G protein coupled receptors (S1PR1-5) or receptor independent, through intra cellular targets such as HDACs and TRAF2, or independent manner. The involvement of S1P signaling has been confirmed in various disease conditions including lung diseases. The SphKs inhibitors and S1PR modulators are currently under clinical trials for different pathophysiological conditions. There is a significant effort in targeting various components of S1P signaling for several diseases. This review focuses on the ways in which S1P signaling can be therapeutically targeted in lung disorders.